Hypolipidemic and hypoglycemic potential of raw, boiled, and sprouted mung beans (Vigna radiata L. Wilczek) in rats. Issue 1 (21st November 2017) - Liyanage, Ruvini; Kiramage, Chathuranga; Visvanathan, Rizliya; Jayathilake, Chathuni; Weththasinghe, Pabodha; Bangamuwage, Ruksheela; Chaminda Jayawardana, Barana; Vidanarachchi, Janak
Abstract: This study was carried out to investigate the hypolipidemic and hypoglycemic potential of raw, boiled, and sprouted mung beans in rats. Oven dried mung bean powders; raw, sprouted, and boiled were included at 30% level in the diet of seven weeks old male Wistar rats maintained for 5 weeks on high (0.5%) cholesterol diet in comparison with control diet. Low serum glucose and triglyceride concentrations ( p  < .05) in raw and processed mung bean diets fed rats were supported by low serum insulin level in both raw mung bean diet and boiled mung bean diet fed rats. Hypoglycemic effect in sprouted mung bean fed rats was supported by higher α‐amylase inhibitory activity and α‐glucosidase inhibitory activity of sprouted mung beans. Increase in serum non‐HDL cholesterol concentration and decrease in HDL cholesterol concentration caused by high cholesterol diet were modulated ( p  < .05) by both boiled and sprouted mung bean diets. Practical applications: Mung bean is a green legume rich in protein, fiber, antioxidants, and phytonutrients. Hypocholesterolemic and hypoglycemic potential of raw mung beans have been shown previously. It is well known that cooking and processing modulate nutritional and biochemical parameters of foods. However, very limited information is available on the effect of processing on functional properties of legumes. Results of this study showed that boiling and sprouting improved the soluble fiber content and hypocholesterolemic potential of mung beans. Thus, the processed mung beans may be more suitable for developing food supplements for patients with hypercholesterolemia.